2016
DOI: 10.1049/iet-nbt.2016.0036
|View full text |Cite
|
Sign up to set email alerts
|

Synthetically modified nano‐cellulose for the removal of chromium: a green nanotech perspective

Abstract: Existing processes for the decontamination of heavy metals from water are found to be cost-prohibitive and energy-intensive which is totally against the sustainable concept of development. Green nanotechnology for water purification for ecosystem management, agricultural and industry is an emerging as leading global priority and occupies better position over the current state of water purification. Herein, the diafunctionalised polyaniline modified nanocellulose composite sorbent (PANI-NCC) has been used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 67 publications
0
6
1
1
Order By: Relevance
“…Apart from these, several studies revolve around the use of different chemical materials to modify CNCs and utilize them as adsorbents for water purification. [67][68][69][70][71][72] An investigation was conducted by Rafieian et al, [42] involving the preparation and characterization of a membrane, consisting of (3 aminopropyl)triethoxysilane or APTESmodified CNC (MCNC) and a nonwoven substrate at the bottom for removing heavy metals like copper ions present in water. It was observed that MCNC was responsible for the improvement of fouling resistance and water flux of the polyethersulfone (PES)/MCNC membrane and increased efficiency in metal ion removal.…”
Section: Removal Of Heavy Metal Ionsmentioning
confidence: 99%
“…Apart from these, several studies revolve around the use of different chemical materials to modify CNCs and utilize them as adsorbents for water purification. [67][68][69][70][71][72] An investigation was conducted by Rafieian et al, [42] involving the preparation and characterization of a membrane, consisting of (3 aminopropyl)triethoxysilane or APTESmodified CNC (MCNC) and a nonwoven substrate at the bottom for removing heavy metals like copper ions present in water. It was observed that MCNC was responsible for the improvement of fouling resistance and water flux of the polyethersulfone (PES)/MCNC membrane and increased efficiency in metal ion removal.…”
Section: Removal Of Heavy Metal Ionsmentioning
confidence: 99%
“…Many researchers use adsorption techniques to remove the HMIs from groundwater [21][22][23][24][25][26] and help to remove the hazardous heavy metals after the contaminated source is detected. The proposed sensor platform can be used as an early warning system to identify the contaminated source at the picomolar range.…”
Section: Introductionmentioning
confidence: 99%
“…BNC as one of the most renewable, natural bio-sorbents, and the biocompatible polymer was characterised by high waterholding capacity and high surface area leading to wide industrial applications [7,8]. BNC has been reported to display a potential application in the pharmaceutical and biomedical fields, where it has been primarily applied for transdermal formulations to improve clinical outcomes [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%